What Is Your Diagnosis? - Y Inakanti; S Kumar (Nepal Journal of Dermatology, Venereology & Leprology)
Seborrhoeic keratosis is slow-growing, sharply demarcated tumour with a fissured or pitted surface.  Its surface may  have a thin greasy scale. It is benign tumour of external ear originating from proliferative epithelial cells. Its most common site ranges from the retro auricular region to the helical rim.